The Order of Caballero de la Luz and the revolutionary triumph of 1959 (Islas, 2024)
Introduction: Studies on the Cuban Revolution have focused on popular participation through the actions of political organizations that led to its triumph, leaving behind the role of long-standing patriotic organizations, such as fraternal associations.Methods: The research was based on documentary analysis of sources produced and preserved primarily by the fraternal association, whose provided information was systematized with existing historiographical studies on the Cuban Revolution.Results: The political support stance of the Orden Caballero de la Luz for the revolutionary triumph of 1959 is revealed through the exemplification of its public declarations in periodical publications, as well as its actions in confronting US defamatory campaigns and providing material and human support for revolutionary efforts.Conclusions: The Orden Caballero de la Luz had a radical political position in favor of the revolutionary triumph of 1959, reflected in public declarations and through its actions in confronting defamatory campaigns and supporting revolutionary measures and laws.
Keywords: Cuban Revolution; Orden Caballero de la Luz; history of Cuba